UPAYA PENINGKATAN KINERJA PELAYANAN KARYAWAN PADA AKADEMI PARIWISATA INDRAPHRASTA YOGYAKARTA - Roberto Mario Kabi Teniwut (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2014)
This research was conducted to see the quality of service the employee division of academic, administrative, financial, library and computer labs at IndraphrastaAcademic Tourism of Yogyakarta. Source of data used are primary and secondary data with a four-month study period. While the methods used are surveys and observations with analysis tools both of SWOT analysis and description. The results of the first, the general implementation of education and training for the employees of each division in the Academic Indraphrasta Tourism Yogyakarta still needs to be improved and developed. Second, the importance of continuing education for employees who have not reached the required standards and the need for recruitment of prospective employees who have the competence, thus meeting the needs of qualified human resources. Third, the need for the activities carried out by the Indraphrasta Academic Tourism of Yogyakarta involving all existing employees. Recomendation that can be given is to transfer power to thepersonnel who have the ability and experience. Secondly, before the candidaterecruitment process should be set in advance the standards of the qualification ofhuman resources required. Third, the need for out bound activities to employees.Fourth, the importance of the leadership role that always keep the employees keepworking optimally in accordance with their competence, for example, share avision. Fifth, the need for periodic meetings with the leaders of two weeks. Sixth,do renewal office equipment. Seventh, the need for promotion and marketingactivities through cooperative relationships with government agencies or private.Recently the need for education and ongoing training for employees in order toimprove performance.